2004
DOI: 10.1002/ana.20233
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cortical TrkA but not p75NTR protein in early‐stage Alzheimer's disease

Abstract: Degeneration of cholinergic nucleus basalis (NB) cortical projection neurons is associated with cognitive decline in late-stage Alzheimer's disease (AD). NB neuron survival is dependent on coexpression of the nerve growth factor (NGF) receptors p75(NTR) and TrkA, which bind NGF in cortical projection sites. We have shown previously a significant reduction of NB perikarya expressing p75(NTR) and TrkA protein during the early stages of AD. Whether there is a concomitant reduction in cortical levels of these rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(189 citation statements)
references
References 78 publications
7
181
0
1
Order By: Relevance
“…It is also worth noting that different studies have found a selective and marked reduction in the expression of cortical TrkA in early and late stages of AD, when compared to age-matched controls [30,68,111]. This seems to occur in the face of stable [30,68,111] or increased [72,113] p75 NTR , and increased pro-NGF [41,121].…”
Section: Igf1-r Neurotrophin Signaling and Ad: A Tale Of Receptors mentioning
confidence: 95%
“…It is also worth noting that different studies have found a selective and marked reduction in the expression of cortical TrkA in early and late stages of AD, when compared to age-matched controls [30,68,111]. This seems to occur in the face of stable [30,68,111] or increased [72,113] p75 NTR , and increased pro-NGF [41,121].…”
Section: Igf1-r Neurotrophin Signaling and Ad: A Tale Of Receptors mentioning
confidence: 95%
“…TrkA, p75, Sortilin (Lu et al, 2005). While a marked decrease of TrkA is assessed in basal forebrain and in cortex (Chu et al, 2001;Mufson et al, 1996Mufson et al, , 1997Mufson et al, , 2000Salehi et al, 1996;Boissiere et al, 1997;Hock et al, 1998;Savaskan et al, 2000;Counts et al, 2004;Ginsberg et al, 2006), p75NGF receptor levels appear to be up-regulated (Hu et al, 2002), downregulated (Kerwin et al, 1992;Salehi et al, 2000;Mufson et al, 2002) or unchanged (Mufson et al, 2003;Ginsberg et al, 2006) in different models of aging and of AD. In addition, an unbalance in TrKA and p75 activity favoring the binding of NGF to p75 and the Ab mediated neuronal death has been recently reported in mild AD patients (Wu et al, 2007) and in in vitro AD neuronal models (Sotthinbundhu et al, 2008;Matrone et al, 2009).…”
Section: Ngf and Its Receptors In Admentioning
confidence: 98%
“…Therefore, investigators have been searching for additional biological markers. The loss of nerve growth factor (NGF) as well as its receptor has been implicated in the loss of cholinergic tone and function in AD and aging [14,33,34]. In MCI patients it was found that basal forebrain levels of TrkA decline 50% compared with age matched controls and that the number of TrkA immunopositive neurons in the basal forebrain correlate well with a number of different cognitive measures [33,34].…”
Section: Introductionmentioning
confidence: 99%